Eculizumab Pharmacokinetics and Pharmacodynamics in Patients With Neuromyelitis Optica Spectrum Disorder - Singh, Pratap; Gao, Xiang; Kleijn, Huub Jan; Bellanti, Francesco; Pelto, Ryan (Frontiers in Neurology, 2021)
Objective: To investigate the pharmacokinetics and pharmacodynamics of the approved 900/1,200 mg dosing regimen for the terminal complement component 5 (C5) inhibitor eculizumab in patients with neuromyelitis optica spectrum disorder (NMOSD). Methods: Data were analyzed from 95 patients with aquaporin-4-IgG-positive NMOSD who received eculizumab during the PREVENT study (ClinicalTrials.gov: NCT01892345). Relationships were explored between eculizumab exposure and free complement C5 concentrations, terminal complement activity, and clinical outcomes. Results: Pharmacokinetic data were well-described by a two-compartment model with first-order elimination, and time-variant body-weight and plasmapheresis/plasma exchange effects. Steady-state serum eculizumab concentrations were achieved by Week 4 and were sustained, with serum trough eculizumab concentrations maintained above the 116 μg/ml threshold for complete complement inhibition throughout 168 weeks of treatment in all post-baseline samples from 89% of patients. Complete inhibition of terminal complement was achieved at Day 1 peak and pre-dosing trough eculizumab concentration in nearly all post-baseline samples assessed (free C5 <0.5 μg/ml in all post-baseline samples from 96% of patients; in vitro hemolysis <20% in all post-baseline samples from 93% of patients). Kaplan–Meier survival analysis of time to first relapse showed separation of eculizumab-treated patients from those receiving placebo, but no separation based on eculizumab exposure quartile, indicating an optimized dose regimen with maximized efficacy. Conclusions: The approved eculizumab dosing regimen (900/1,200 mg) for adults with aquaporin-4-IgG-positive NMOSD is confirmed by rigorous quantitative model-based analysis of exposure–response. The data demonstrate that eculizumab's mechanism of action translates into clinical effect by achieving rapid, complete, and sustained terminal complement inhibition.